Relationships between the Dark Tetrad Traits and tendency towards corruptive behavior: The mediating effect of corruptive rationalizations and thhe mediating effect of corruptive rationalizations and the moderating effect of organizational ethical virtues - Komanović, Lidija; Dinić, Bojana M. (Psihološka istraživanja, 2024)
The Dark Triad/Tetrad traits are associated with various counterproductive work behaviors, including unethical behaviors such as a tendency towards corruption. The aim of this research was to further examine the mechanism and conditions under which dark traits are linked to corruption tendency. Specifically, the mediating effect of corruptive rationalizations and the moderating effect of the organization’s ethical culture, i.e., organizational ethical virtues, were investigated, including the effect of moderated mediation. The sample consisted of 252 employees (58.3% female) aged 20 to 64. The results showed that all dark traits, except psychopathy, have a significant direct and positive effect on corruption tendency when considered all together in a regression model. Corruptive rationalizations are a significant mediator between Machiavellianism, psychopathy, and sadism, on one side, and corruption tendency, on the other side. Unexpectedly, the organizational ethical virtues are not a significant moderator in the relationship between the dark traits and corruption tendency. However, they are a significant moderator between Machiavellianism and corruptive rationalizations but in unexpeted way, i.e., the link between Machiavellianism and corruptive rationalizations is stronger in cases of more pronounced ethical virtues in the organization. The results generally indicated a higher importance of individual factors of corruptive behavior, in contrast to organizational factors, and provided additional insight into the complex relationships between the individual factors and corruptive behavior.